Estimation of Submerged Aquatic Vegetation Height and Distribution in Nova Avanhandava Reservoir (São Paulo State, Brazil) Using Bio-Optical Modeling - Rotta, Luiz Henrique da Silva [UNESP] (2015)
Semi-analytical models have been developed to remove the water column influence and then retrieve the bottom reflectance in water bodies in order to study submerged targets. However, the majority of these models were elaborated for oceanic and coastal waters, in other words, there are still limited studies about the retrieval of the bottom response from remote sensing in continental aquatic environments. The reason for that is the complexity of those environments as they present high concentrations of dissolved and suspended constituents, which make it difficult to detect the bottom signal. The objectives of this thesis were: to assess the availability of sub-aquatic radiation in the water column and the total suspended solids concentration (TSS) in the Nova Avanhandava reservoir in order to analyze their influence on the SAV (Submerged Aquatic Vegetation) development; to recover the bottom albedo and generate bio-optical models to estimate the aquatic submerged vegetation height and position in the Nova Avanhandava reservoir; and finally, to use and assess the bio-optical models performance by using multi-spectral imagery (SPOT-6). Hyperspectral data were collected by using the radiometer RAMSES - TriOS. It was found that studies on subaquatic radiation availability measured by the vertical attenuation of downwelling irradiance in the water column can aid in understanding SAV behaviour in tropical reservoirs and, therefore, contribute to its management. SPOT-6 image, acquired on July the 9th of 2013, was atmospherically corrected by the empirical line method...